Ergot alkaloids: structure diversity, biosynthetic gene clusters and functional proof of biosynthetic genes - Wallwey, Christiane; Li, Shu-Ming (Natural product reports, 2011)
Ergot alkaloids are toxins and important pharmaceuticals which are produced biotechnologically on an industrial scale. They have been identiﬁed in two orders of fungi and three families of higher plants. The most important producers are fungi of the genera Claviceps, Penicillium and Aspergillus (all belonging to the Ascomycota). Chemically, ergot alkaloids are characterised by the presence of a tetracyclic ergoline ring, and can be divided into three classes according to their structural features, i.e. amide- or peptide-like amide derivatives of D-lysergic acid and the clavine alkaloids. Signiﬁcant progress has been achieved on the molecular biological and biochemical investigations of ergot alkaloid biosynthesis in the last decade. By gene cloning and genome mining, gene clusters for ergot alkaloid biosynthesis have been identiﬁed in at least 8 different ascomycete species. Functions of most structure genes have been assigned to reaction steps in the biosynthesis of ergot alkaloids by gene inactivation experiments or biochemical characterisation of the overproduced proteins.